The Past Through Stone: A Comparative Analysis of Umpak Songo with Contemporary Architectural Structures in East Java - Nabila, Imrotun; Wildan, Akhmad; Nadiah, Putri (SINGOSARI: Jurnal Perkumpulan Prodi Pendidikan Sejarah Se-Indonesia (P3SI) Wilayah Jawa Timur, 2025)
This study aims to investigate the architectural significance of Umpak Songo in East Java through a comparative analysis with contemporary building structures. Umpak Songo, characterized by a configuration of nine stone foundations, is analyzed in the context of its structural function and possible representation of ritual or cosmological practices of ancient societies. Through comparison with architectural elements from the same time period in East Java, this study explores the continuities, differences, and potential distinctiveness of Umpak Songo. The results show that Umpak Songo not only serves as a supporting element of the building, but also stores important information about local architectural adaptations and may reflect aspects of the culture and beliefs of the society at that time. This study contributes to a deeper understanding of the diversity of ancient architecture in East Java and highlights the importance of comparative analysis of architectural details in reconstructing past history and culture.